Relationship between fundus of the eye examination and arterial stiffness - Barbosa, Eduardo Costa Duarte; Klein, Ana Carolina Storch; Klein, Julia Gabriela Storch; Möller, Camila Samrsla; Manfio, Eliane Fátima; Eibel, Bruna; Mengue, Carolina da Silva (Frontiers in Cardiovascular Medicine, 2025)
This review addresses the correlation between arterial stiffness, measured by pulse wave velocity (PWV), and retinal microvascular changes, highlighting the retina as an important accessible window for inferences about cardiovascular health. Arterial stiffness, intrinsically linked to vascular aging and several comorbidities, results in damage to the microcirculation, including ocular vasculature, which can act as a predictor of cardiovascular and cerebrovascular outcomes. The review highlights the relationship between PWV assessment and funduscopic examination, with the aim of improving diagnostic accuracy and optimizing the clinical application of these tools in the management of cardiovascular and ophthalmological diseases, thus promoting more effective and early intervention.